2023
DOI: 10.1182/bloodadvances.2022009274
|View full text |Cite
|
Sign up to set email alerts
|

Human herpesvirus 6–specific T-cell immunity in allogeneic hematopoietic stem cell transplant recipients

Abstract: Human Herpesvirus-6 (HHV-6) can reactivate after allogeneic Hematopoietic Stem Cell Transplantation (allo-HSCT), and may lead to severe symptoms. HHV-6-specific immune responses after HSCT are largely unexplored. We conducted a prospective observational study on 208 consecutive adult patients who received allo-HSCT, to investigate HHV-6 reactivations and specific immune responses. IFN-γ-producing HHV-6-specific T cells were quantified by ELISpot assay. "HHV-6 reactivation" occurred in 63% of patients, at a med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
3
9
0
Order By: Relevance
“…Two previous studies have reported a protective effect of higher lymphocyte counts (CD3+ lymphocytes ≥ 200/µL) against HHV6 reactivation. 35,39 Consistent with these results, our analysis revealed that patients with a low ALC on day +30 (\< 290/µL) had a higher incidence of HHV6 reactivation. This finding may serve as a valuable tool to help clinicians identify patients at higher risk of HHV6 reactivation, for whom a closer monitoring of HHV6 by PCR might be considered.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Two previous studies have reported a protective effect of higher lymphocyte counts (CD3+ lymphocytes ≥ 200/µL) against HHV6 reactivation. 35,39 Consistent with these results, our analysis revealed that patients with a low ALC on day +30 (\< 290/µL) had a higher incidence of HHV6 reactivation. This finding may serve as a valuable tool to help clinicians identify patients at higher risk of HHV6 reactivation, for whom a closer monitoring of HHV6 by PCR might be considered.…”
Section: Discussionsupporting
confidence: 88%
“…Regarding clinically significant HHV6 infections, our study demonstrates a low incidence (7%), whereas one study on HAPLO HCT with PT-Cy reported a rate of 16%, 18 and another analysis of PT-Cy with non-HAPLO donors reported a rate of 24%. 35 Taken together, our findings suggest the combination of ATG and PT-Cy does not present a higher risk of HHV6 reactivation or clinically significant HHV6 infections compared to PT-Cy without ATG in the HAPLO HCT setting.…”
Section: Discussionsupporting
confidence: 56%
“…Fortunately, HHV-6B encephalitis is still relatively rare, occurring in 1–3% of HCT recipients, though its incidence may be higher in specific groups (e.g., cord blood and T cell depleted transplants) [ 4 , 6 , 15 ]. Risk factors for reactivation and disease include umbilical cord blood transplant, T cell depleted allografts, human leukocyte antigen-mismatched or unrelated donors, acute GVHD and treatment with glucocorticoids [ 4 , 6 , 13 , 15 , 20 ].…”
Section: Epidemiology Of Hhv-6b After Allogeneic Hctmentioning
confidence: 99%
“…PTCy for GVHD prophylaxis is more widely used in the setting of increasingly performed haploidentical and unrelated donor transplants [ 23 ]. PTCy is associated with increased risk for infections post-HCT in several studies [ 20 , 24 , 25 , 26 , 27 ]. A study of 2765 HCT recipients by the Center for International Blood and Marrow Transplantation Research showed an association between PTCy use and increased risk for non-CMV herpesvirus infection, primarily driven by HHV-6B, which was in turn associated with increased non-relapse mortality [ 24 ].…”
Section: Epidemiology Of Hhv-6b After Allogeneic Hctmentioning
confidence: 99%
See 1 more Smart Citation